DIPLOMASI INFORMAL PENYELESAIAN KONFLIK LAUT CINA SELATAN ILMU HUBUNGAN INTERNASIONAL FAKULTAS ILMU SOSIAL DAN ILMU POLITIK SEBAGAI PENDEKATAN DALAM PROSES - , Claudia Conchita Renyoet ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to describe the dynamics of the South China Sea territorial dispute are clear and to explore the entire mechanism of diplomacy, especially in the informal diplomatic approach to conflict resolution of disputes in the South China Sea region. Study of the mechanisms of informal diplomacy is expected to be a good alternative approach in the dispute resolution process between countries where the informal diplomacy plays an important role when an official or the first track diplomacy and mediation efforts of others is not easily done in a dispute or conflict resolution process. This research using descriptive method. Where to collect detailed factual information that describes the existing symptoms, identify the problem or check the conditions and practices in force, making comparisons or evaluations, and determine what other people do in the face of similar problems and learn from experience to establish plans and decisions the time will come. The data used in this study is secondary data is data which obtained from various sources of literature related to the research conducted by the author. The data in this study were obtained from the data collection from various official publications consist of books, documents, journals, and newspapers. Data from the author analyzes the results of qualitative techniques, which emphasize the data analysis of qualitative data. The results showed that the diplomatic approach of the development of informal dispute since seen this approach applied to the year 1990 has brought a significant results and positive influence in the process of resolving the territorial dispute itself. With this informal approach to diplomacy, military conflict between countries can be prevented since the year 1990-2011. This is because the nature of diplomacy is not formal so that it can be accepted by all the disputing countries where diplomatic relations between the disputing countries is not good so the formal diplomacy difficult to apply the dispute resolution process